Lighting the way: Forces driving the diversification of bioluminescent signalling in sea fireflies. Issue 8 (29th March 2021) - DeLeo, Danielle M.; Bracken‐Grissom, Heather D.
Abstract : Understanding the drivers of diversification and processes that maintain biodiversity remains a central theme of evolutionary biology. However, these efforts are often impeded due to disparities across species and environments and the genetic complexity underlying many traits. The factors driving biodiversity can be more readily understood by focusing on the genetics of diversification, of one or few genes shared across species, with large influence over an organism's phenotype (Templeton, 1981; Wright, 1984). In this pursuit, previous studies often focus on the selective pressures that impact phenotypic diversity (Brawand et al., 2014; Yokoyama et al., 2015), often overlooking the contribution of neutral processes (i.e., genetic drift). In this issue of Molecular Ecology, Hensley et al. (2020) use an integrative approach, including RNA sequencing, in vitro protein expression and spectral measurements, to explore the drivers behind the diversification of bioluminescent signalling in cypridinid ostracods (Figure 1). Typical bioluminescent reactions primarily include an enzyme (luciferase) and substrate (luciferin). By focusing on a single gene, this study traces the molecular evolution of (c)luciferase in sea fireflies, elucidating diverse signatures of selection, drift and constraint to decipher the link between genotype and phenotype of their bioluminescent emissions.